Perception of odd prices in a Post-Soviet country: an impact of the ideology of planned economy - Dikcius, Vytautas; Katkuviene, Kristina (Journal of Business Economics and Management, 2014)
This empirical paper analyzes the perception of odd prices in a Post-Soviet country. Two different streams of perception of odd prices are developed – a level effect and an image effect. The paper focuses on the latter effect. The authors analyze the perception of odd prices in different categories of products – convenience goods, clothes and domestic appliances. In addition, four different levels of a price were used in order to measure the perception of a price having various price levels. The results showed that Lithuanians have a different attitude about odd prices compared with the research in developed countries. At the same time the survey showed that the respondents’ experience related to odd prices fits the results of the research from developed countries. Moreover, the participants of the survey intuitively perceived odd prices as something negative and associated odd prices with cheating in the case of convenience products, or with discounted products in the case of shopping goods. This research demonstrates that companies should not practice nine-ending pricing widely since the respondents associated odd prices were preferred more in the case of cheap products (up to 10 LTL) than expensive products, and odd prices were related with discounted products in the case of shopping goods.